Efficacy of low dose rectal diclofenac for preventing post‐endoscopic retrograde cholangiopancreatography pancreatitis: Propensity score‐matched analysis. Issue 4 (16th October 2020) - Tomoda, Takeshi; Kato, Hironari; Miyamoto, Kazuya; Matsumi, Akihiro; Ueta, Eijiro; Fujii, Yuuki; Saragai, Yousuke; Yamazaki, Tatsuhiro; Uchida, Daisuke; Matsumoto, Kazuyuki; Horiguchi, Shigeru; Tsutsumi, Koichiro; et al.
Abstract : Background: Acute pancreatitis is a major adverse event of endoscopic retrograde cholangiopancreatography (ERCP). Rectal administration of non‐steroidal anti‐inflammatory drugs (NSAIDs) decreases the incidence of post‐ERCP pancreatitis (PEP). However, the efficacy of low dose rectal NSAIDs for preventing PEP remains controversial. Methods: We performed a retrospective study of 301 patients with native papilla and a body weight of <50 kg who underwent ERCP between September 2010 and October 2019. After July 2016, a 25 mg dose of rectal diclofenac was routinely administered within 15 min before ERCP (NSAIDs group, n  = 72) and the control group ( n  = 229) consisted of patients undergoing ERCP before this date without treatment. We compared the incidence of PEP between the two groups using propensity score matching. Results: A total of 66 pairs of patients in each group were selected. The patients and procedural‐related factors were similar in both groups. In total, 15 patients (11.4%) developed PEP: 12.1% (8/66) in the NSAIDs group and 10.6% (7/66) in the control group (Odds ratio (OR) 1.2; 95% confidence interval (CI) 0.4–3.5; P  = 0.78). There was no significant difference in incidence of other adverse events related to ERCP between the two groups. Conclusions: Prophylactic administration of a 25 mg dose of rectal diclofenac did not reduce the incidence of PEP in patients with a native papilla and a body weight of <50 kg in this study and a certain dose of rectal NSAIDs, such as a 100‐mg dose, should be administered regardless of body weight to prevent PEP.